Revisiting Psyllocarpus intermedius (Rubiaceae, Spermacoceae) : an updated description with a new synonym - Martins Do Carmo, João Afonso (2023)
Fil: Martins Do Carmo, João Afonso. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Botánica del Nordeste; Argentina.